A cross-grid structure functionalized silica gel material and its preparation method and application
By using cross-grid structures to functionalize silica gel materials during seawater uranium extraction, the problems of targeted adsorption of existing adsorbents in seawater, high-efficiency adsorption under low concentration conditions are solved, and the effects of high-selective adsorption of uranyl ions and high-efficiency uranium extraction are achieved.
Patent Information
- Application Number
- CN202411568125.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-05
AI Technical Summary
It is difficult for existing adsorbents to achieve targeted adsorption, efficient adsorption and high selectivity under low concentration conditions during the process of extracting uranium in seawater, especially affected by competition from vanadium ions.
The cross-grid structure is used to functionalize the silica gel material, which forms a cross-grid structure with adjustable pore size through the reaction of functionalized polyamine segment silica gel and the Schiff base of aromatic cyano or aromatic carboxylic compounds, enhancing the highly selective adsorption of uranyl ions.
Highly selective adsorption of uranyl ions is achieved, and uranium can be adsorbed efficiently under low concentration conditions, and the selectivity to uranium and vanadium is improved through the screening effect, with high adsorption capacity and strong cycle stability.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a cross-grid structure functionalized silica gel material and a preparation method and application thereof. Background Art
[0002] The environmental conditions of the seawater system are extremely complex. Although the uranium content is high, the concentration is extremely low (~3.3ppb). Excessive interfering metal ions and their compounds make the extraction of uranium extremely difficult. Among the existing common separation methods, compared with membrane separation, ion exchange, chemical precipitation, electrochemical methods, etc., the adsorption method has the advantages of simple operation, strong practicality, and simple adsorbent regeneration. It is one of the most commonly used and effective technologies.
[0003] As traditional adsorption materials, silicon-based materials stand out among carbon materials, resins, biomass, crystalline materials, etc. due to their inorganic-organic hybridization ability, stable three-dimensional structure and easy functionalization design advantages. Their low cost and simple synthesis conditions also enable silicon-based materials to achieve industrial large-scale production.
[0004] Based on the above, the adsorbent used for uranium extraction from seawater must have the following characteristics:
[0005] (1) Targeted adsorption
[0006] For the uranium extraction process from seawater, the adsorption of uranium by adsorbents in complex seawater systems is usually an inner-layer complexation that is not affected by ionic strength. Among them, Ca and Mg will form complexes with uranyl carbonate anions; since the molar concentration of iron ions in seawater is 3 times higher than that of uranium, it is also considered to be one of the main competing ions; most commercial adsorbents are amidoxime polymers, and their high adsorption capacity for vanadium (V) makes vanadium the biggest challenge in the current seawater uranium extraction process. The complexity of the above influencing factors requires that the design of the adsorbent needs to have functional groups that have a certain targeting effect on uranyl ions;
[0007] (2) Efficient adsorption under low concentration conditions
[0008] The concentration of uranium in the ocean is at the ppb level, which is quite different from the ppm level metal ion adsorption experiments in the laboratory. Many crystalline materials (such as MOF, COF, etc.) used as adsorbents in metal ion thermodynamic adsorption experiments show extremely high adsorption capacity, but the overly narrow and regular pores under low concentration conditions cannot guarantee site accessibility, so the actual application in seawater is not effective. Therefore, the design of uranyl ion adsorbents in seawater systems needs to have high group loading and cross-network structure to allow uranyl ions to pass freely, thereby improving group utilization and achieving efficient adsorption in extremely low concentration systems;
[0009] (3) High selectivity
[0010] It is difficult to achieve efficient selection of uranyl ions by relying solely on groups, and the existence form and chemical properties of vanadium ions and uranyl ions in seawater are very similar, so there is competitive adsorption. Therefore, the key to improving uranium selectivity is to improve uranium-vanadium selectivity. The example form of uranyl ions in seawater is (UO2)3(OH)3 + , whose hydrated ion radius is 10.37Å, while the hydrated ion radius of vanadium ions in seawater is greater than 16Å. It is an extremely effective strategy to improve selectivity by screening the adsorbed substances with the help of the pore size of the adsorbent. Summary of the invention
[0011] In order to solve the above technical problems, the purpose of the present invention is to provide a cross-grid structure functionalized silica gel material and a preparation method and application thereof; the present invention adopts functionalized polyamine segment silica gel as a material matrix, uses aromatic cyano compounds or aromatic carboxyl compounds as "bridges" to connect the functionalized long chains on the surface of the silica gel in pairs, and further divides its spatial structure on the basis of the original three-dimensional structure to form a cross-grid functionalized silica gel with adjustable pore size; the silica gel material has an adjustable network structure and abundant imine bonds, realizes high selective adsorption of uranyl ions, can screen uranyl ions and vanadium ions, and has a high adsorption capacity for uranyl ions and strong adsorption cycle stability.
[0012] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0013] On one hand, the present invention provides a cross-grid structure functionalized silica gel material, which is obtained by reacting a compound represented by structural formula I with an aromatic aldehyde or aliphatic aldehyde compound as a bridging agent and an aromatic cyano or aromatic carboxyl compound with a diamino group through a Schiff base reaction;
[0014] Wherein, structural formula I is:
[0015] [(O 3 / 2 )Si(CH2)3NH[C2H4NH] p-1 C2H4NH2] a [(O 4 / 2 )Si] b [(O 3 / 2 )Si(CH2) m L] c [MSi(O 3 / 2 )] d ; Wherein L is -CN or S(CH2) y CN, y is an integer from 2 to 6; M is a substituent group selected from C 1-22 Alkyl, C 2-22 Alkenyl or C 1-22alkylaryl; m is an integer from 2 to 12; p is an integer from 2 to 99; a, b, c, d are all integers, and the ratio of a+c:b is between 0.00001 and 100000; a and b are always present, and when c is greater than zero, the ratio of c to a+b is between 0.000001 and 10; silicon atoms, hydrogen atoms, straight or branched C atoms of other groups in formula I are present; 1-22 Alkyl, terminal group R 2 SiO 1 / 2 , cross-linking agent or chain R q Si(OR 1 ) g O k / 2 One or more of saturates the free valences of the silicate oxygen atoms, where R and R 1-2 Selected from linear or branched C 1-12 Alkyl, aryl or C 1-22 Alkyl aryl; k is an integer from 1 to 3, q is an integer from 1 to 2, g is an integer from 0 to 2, and satisfies g+k+q=4, and when end groups, crosslinking agents and / or polymer chains are present, their molar ratio to a+b+c+d is between 0 and 999:1.
[0016] Preferably, p is an integer from 2 to 9.
[0017] Furthermore, the aromatic aldehyde or aliphatic aldehyde compound is an olefin compound or a halogen substituted compound, and its structural formula is:
[0018] or ;
[0019] In the above structural formula, R a , R b , R c , R d , R', R'', R''' are selected from hydrogen, C 1-22 Alkyl, C 2-22 Alkenyl or C 1-22 One of the alkylaryl groups, X is a halogen; w is 0 or 1, and v is an integer from 0 to 7.
[0020] Furthermore, the structural formula of the aromatic cyano or aromatic carboxyl compound is one of the following structural formulas:
[0021] ;
[0022] In the above structural formula, T is one of alkenyl, aryl or its derivatives, n is an integer from 0 to 2; R1, R2, R3, R4, R1', R2', R3', R4' are respectively selected from one of hydrogen, -NH2, -CN, -COOH, and at least one of the corresponding structural formulas is -CN or -COOH.
[0023] Furthermore, the structural formula A of the cross-grid structure functionalized silica gel material is one of the following structural formulas:
[0024] ;
[0025] In the above structural formula, R a , R b , R c , R d , R', R'', R''' are respectively selected from one of hydrogen, C1-22 alkyl, C2-22 alkenyl or C1-22 alkylaryl; w is 0 or 1, v is an integer from 0 to 7; T is one of alkenyl, aryl or their derivatives, and n is an integer from 0 to 2; R1, R2, R3, R4, R1', R2', R3', R4' are respectively selected from one of hydrogen, -NH2, -CN, -COOH, and at least one of the corresponding structural formulas is -CN or -COOH; II is the structure remaining after the compound shown in structural formula I reacts with an aromatic aldehyde or a fatty aldehyde compound.
[0026] Furthermore, when an aromatic cyano compound is selected as the raw material, the product after the Schiff base reaction (the silica gel material shown in the above-mentioned structural formula A containing -CN) can be further subjected to a hydrolysis reaction, and the structural formula of the obtained cross-grid structure functionalized silica gel material is a variation of the structural formula A containing -CN, that is, the -CN in the structural formula A is changed to -COOH.
[0027] Another aspect of the present invention provides a method for preparing the cross-grid structure functionalized silica gel material, comprising the following steps:
[0028] (1) (R 3 O)3Si(CH2)3X' and the corresponding amine NH2[C2H4NH] p H reacts to form silane (R 3 O)3Si(CH2)3NH[C2H4NH] p H, X' are halogen elements, R 3 Selected from C 1-22 Alkyl, preferably C 1-6 alkyl;
[0029] (2) The silane coupling agent prepared in step (1) and the cyanosilane coupling agent (R 5 O)3Si(CH2) m L and / or MSi (OR 4 )3 is grafted onto the surface of silica gel to obtain a compound shown in structural formula I; wherein L is -CN or S(CH2) y CN, m is an integer from 2 to 12, y is an integer from 2 to 6; R4 , R 5 Selected from C 1-22 Alkyl, preferably C 1-6 Alkyl; wherein the solvent is a hydrocarbon, an aromatic, an alcohol or water;
[0030] (3) subjecting the compound of structural formula I obtained in step (2) to a reflux reaction with an aromatic aldehyde or an aliphatic aldehyde compound under certain conditions to obtain a functionalized silica precursor;
[0031] (4) The functionalized silica precursor prepared in step (3) is mixed with an aromatic cyano compound or an aromatic carboxyl compound having a diamino group in a solvent, and after reflux reaction at a certain temperature for a certain period of time, the precipitate is filtered, washed, and dried to obtain a cross-grid structured functionalized silica material.
[0032] Furthermore, when an aromatic cyano compound is selected, the product obtained in step (4) is further mixed with an acid in deionized water and then heated and stirred for a certain period of time. The precipitate obtained by the reaction is filtered, washed, centrifuged, and dried to obtain a further carboxylated cross-grid structure functionalized silica gel material. The acid is a mixed acid; the mass ratio of the product obtained in step (4) to the volume of the mixed acid is 1g:(5-50)mL, and the mixed acid is composed of concentrated sulfuric acid and glacial acetic acid, and the volume ratio is 3:1; the stirring reaction temperature is 90-120°C, and the reaction time is 12-24h.
[0033] Furthermore, the reaction temperature of step (1) is 20-160°C, and the reaction time is 0.5-24h; in step (1), (R 3 O)3Si(CH2)3X' and amine NH2[C2H4NH] p The molar ratio of H is 1:1.5-6, and X' is preferably chlorine or bromine.
[0034] Furthermore, the silica gel grafting reaction temperature in step (2) is 20-160°C, and the reaction time is 0.5-24h; the solvent in step (2) is selected from at least one of toluene, xylene, heptane, ethanol, and methanol; at the end of the reaction, the composition is separated by filtration or centrifugation, and then fully washed to remove any residual reactants, and finally dried. The silica gel grafting reaction process can be widely used in commercially available silica gel (amorphous or spherical silica gel, preferably spherical silica gel); the silica gel particle size ranges from 5 to 30 nanometers; and the silica gel has a widely distributed known pore size, preferably a pore size between 20 and 100Å.
[0035] Furthermore, the reaction temperature of step (3) is 60-100° C., and the reaction time is 3-24 h. In step (3), the mass ratio of the amount of aromatic aldehyde or aliphatic aldehyde (olefin compound or halogen substituted product of the two) compound to the compound represented by structural formula I is (0.01-10) mol:1 g.
[0036] In step (3), the aromatic aldehyde or fatty aldehyde compound is prepared in advance into a 10-50% NN dimethylformamide solution, the initiator used in the reaction in step (3) is azobisisobutyronitrile, and after the reaction is completed, it is washed with deionized water to neutrality to obtain aldehyde-functionalized silica gel.
[0037] The reaction temperature of step (4) is 50-80°C, the reaction time is 2-12h; the ratio of the amount of the aromatic cyano compound or aromatic carboxyl compound with a diamino group to the amount of the aromatic aldehyde or aliphatic aldehyde compound is 0.01-0.5:1. The solvent in step (4) is preferably at least one of ethanol, dimethyl sulfoxide, dichloromethane, acetonitrile, chloroform, and N,N-dimethylformamide; a catalyst is also added in step (4), and the catalyst is preferably an aqueous solution of acetic acid with a concentration of 3-12M.
[0038] The cross-grid structure functionalized silica gel material of the present invention has a cross-grid structure with adjustable pore size, and the pore size distribution is within 10-18Å.
[0039] The present invention further provides an application of the cross-grid structure functionalized silica gel material. Specifically, the cross-grid structure functionalized silica gel material can be used as an adsorbent to adsorb uranium elements, such as uranium elements in seawater; further, the cross-grid structure functionalized silica gel material can be used as an adsorbent in the seawater uranium extraction process, and for separating uranyl ions and vanadium ions.
[0040] The beneficial effects of the present invention are:
[0041] (1) The present invention connects an aromatic cyano compound or an aromatic carboxyl compound with a para-diamino group to N-containing sites on different silica gel segments to form a cross-grid between the chains. By controlling the number of benzene rings of the aromatic cyano or aromatic carboxyl monomers and the chain length of the aromatic aldehyde or aliphatic aldehyde (olefin compounds or halogen substitutes of the two) compounds, the mesh aperture is adjustable within 10-18Å, and uranyl ions and vanadium ions can be screened to achieve highly selective adsorption of uranyl ions.
[0042] (2) Aromatic aldehydes or aliphatic aldehydes (olefin compounds or halogen-substituted products of the two) compounds are used as bridging agents to connect the silica gel segments and aromatic cyano compounds or aromatic carboxyl compounds. The aldehyde group and the amino group form an imine bond through a Schiff base reaction. The N atom in the imine bond carries a lone pair of electrons, which can coordinate with the uranyl ion, thereby achieving targeted capture of the uranyl ion.
[0043] (3) The present invention utilizes the multifunctional amino-functionalized silica gel material shown in structural formula I as a carrier, and utilizes the multiple amine groups contained therein to react with aromatic aldehydes or fatty aldehyde compounds, thereby introducing more aldehyde groups, effectively improving the loading rate of aromatic cyano compounds or aromatic carboxyl compounds, and further improving the carboxyl conversion rate.
[0044] (4) When an aromatic cyano compound is selected as the raw material, the silica gel material obtained after the Schiff base reaction of the present invention can be further subjected to a hydrolysis reaction, wherein the cyano group is hydrolyzed into a carboxyl group, thereby obtaining a further carboxylated cross-grid structure functionalized silica gel material. The conversion of the carboxyl group enhances the hydrophilicity of the material, and the use in a seawater system helps the adsorbent to quickly and fully contact with the uranyl ions, thereby further improving the adsorption efficiency. DETAILED DESCRIPTION
[0045] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] Preparation of amino-functionalized silica gel shown in structural formula I: 0.5 mol of triethylenetetramine and 0.25 mol of (3-chloropropyl)trimethoxysilane were placed in a 500 mL three-necked flask, stirred and refluxed at 100° C. for 4 h, 50 mL of methanol was added and stirred and refluxed for 1 h, and after cooling, the resulting reactant was put into a mixture of xylene (125 ml) and spherical silica gel (100 g, 200-500 μm), and 3-cyanopropyltrimethoxysilane (0.25 mol) was added, and refluxed at 150° C. for 6 h. After cooling, it was filtered, washed with ethanol 5 times and then dried to obtain a compound shown in structural formula I, wherein p is 3, m is 3, L is -CN, a, b, and c are all present, and d is zero.
[0048] Example 1-1
[0049] Accurately weigh 20 g of the amino-functionalized silica gel of structural formula I prepared in Example 1, add 200 ml of 30% acrolein N,N-dimethylformamide solution prepared in advance, mix well and place in a 500 mL three-necked flask, add 0.1 g of azobisisobutyronitrile as an initiator, condense and reflux at 70° C. under nitrogen protection for 3 h, filter, wash with N,N-dimethylformamide 5 times and dry to obtain a functionalized silica gel precursor (aldehyde-functionalized silica gel).
[0050] 10 g of functionalized silica precursor was accurately weighed, and 100 mL of acetonitrile and 2,5-dicyano-p-phenylenediamine (8 g, 0.05 mol) and 12 M acetic acid aqueous solution were added as a catalyst. After thorough mixing, the mixture was reacted at 70 °C for 3 h. After filtering, the mixture was washed several times with ethanol and dried to obtain a cross-grid structured functionalized silica material as shown in the following structural formula.
[0051] ;
[0052] Wherein w=0, v=0, n=0, R', R''' are all H; R1, R4 are all -CN, R2, R3 are all H.
[0053] Example 1-2
[0054] The cross-grid structure functionalized silica gel material obtained in Example 1-1 was added with 100 mL of deionized water, 1 mL of concentrated sulfuric acid and 0.3 mL of glacial acetic acid, heated and stirred at 110°C for 6 h, cooled to room temperature, filtered and collected the precipitate, washed with deionized water until neutral, and then dried to obtain a further carboxylated cross-grid structure functionalized silica gel material. The structural formula of the cross-network structure functionalized silica gel material in Example 1-2 is a variation of the structural formula of Example 1-1, specifically, -CN in the structural formula of Example 1-1 is converted to -COOH.
[0055] Examples 1-3
[0056] Accurately weigh 20 g of the amino-functionalized silica gel of structural formula I prepared in Example 1, add 200 ml of a 30% N,N-dimethylformamide solution of 4-vinylbenzaldehyde prepared in advance, mix well and place in a 500 mL three-necked flask, add 0.1 g of azobisisobutyronitrile as an initiator, condense and reflux at 70 ° C under nitrogen protection for 3 h, filter, wash with N,N-dimethylformamide 5 times and dry to obtain a functionalized silica gel precursor.
[0057] Accurately weigh 10 g of the product prepared in the previous step, add 100 mL of methanol solution, and continue to add 4,4'-diaminobiphenyl-3,3'-dicarbonitrile (0.05 mol) and 12 M acetic acid aqueous solution as a catalyst. After thorough mixing, react at 70 °C for 3 h, filter, wash several times with anhydrous ethanol and dry.
[0058] 100 mL of deionized water, 1 mL of concentrated sulfuric acid and 0.3 mL of glacial acetic acid were added to the prepared product, heated and stirred at 110° C. for 6 h, cooled to room temperature, filtered and collected the precipitate, washed with deionized water until neutral, and then dried to obtain a cross-grid structure functionalized silica gel material shown in the following structural formula.
[0059] ;
[0060] Where w=1, v=0, n=1, R a , R b , R c , R d , R', R'', R''' are all H, R1 is -COOH, R2, R3, R4 are all H, T is .
[0061] Example 2
[0062] Preparation of amino-functionalized silica gel shown in structural formula I: 0.5 mol of tetraethylenepentamine and 0.25 mol of (3-chloropropyl)trimethoxysilane were placed in a 500 mL three-necked flask, stirred and refluxed at 125° C. for 4 h, 50 mL of methanol was added and stirred and refluxed for 1 h, and after cooling, the resulting reactant was put into a mixture of xylene (125 ml) and spherical silica gel (100 g, 200-500 μm), refluxed at 100° C. for 6 h, filtered after cooling, washed with ethanol 5 times and then dried to obtain a compound shown in structural formula I, wherein p is 4, m is 3, a and b are both present, and c and d are zero.
[0063] Example 2-1
[0064] Accurately weigh 20 g of the amino-functionalized silica gel of structural formula I prepared in Example 2, add 200 ml of 30% pentenal N,N-dimethylformamide solution prepared in advance, mix well and place in a 500 mL three-necked flask, add 0.1 g of azobisisobutyronitrile as an initiator, condense and reflux at 70 ° C under nitrogen protection for 3 h, filter, wash with N,N-dimethylformamide 5 times and dry to obtain aldehyde-functionalized silica gel.
[0065] Accurately weigh 10 g of the product prepared in the previous step, add 100 mL of methanol solution, continue to add 2,2'-diaminobiphenyl-4,4'-dicarboxylic acid (0.05 mol) and 12 M acetic acid aqueous solution as a catalyst, mix thoroughly, react at 70 ° C for 3 h, filter, wash several times with anhydrous ethanol and dry to obtain a cross-grid structure functionalized silica gel material shown in the following structural formula.
[0066] ;
[0067] Wherein w=0, v=2, n=0, R', R'', R''', R2, R3, R4, R2', R3', R4' are all H, and R1 and R1' are -COOH.
[0068] Example 2-2
[0069] Accurately weigh 20 g of the amino-functionalized silica gel of structural formula I prepared in Example 2, add 200 ml of a 30% N,N-dimethylformamide solution of 4-vinylbenzaldehyde prepared in advance, mix well and place in a 500 mL three-necked flask, add 0.1 g of azobisisobutyronitrile as an initiator, condense and reflux at 70° C. under nitrogen protection for 3 h, filter, wash 5 times with N,N-dimethylformamide and dry to obtain aldehyde-functionalized silica gel.
[0070] Accurately weigh 10 g of aldehyde-functionalized silica gel and add 100 mL of acetonitrile and 3,3'-diaminobiphenyl-4,4'-dicarboxylic acid (0.05 mol) and 12 M acetic acid aqueous solution as a catalyst. After thorough mixing, react at 70°C for 3 h. After filtering, wash with ethanol several times and dry to obtain a cross-grid structure functionalized silica gel material shown in the following structural formula.
[0071] ;
[0072] Where w=1, v=0, n=0, R a , R b , R c , R d , R', R'', R''', R2, R3, R4, R2', R3', and R4' are all H, and R1 and R1' are -COOH.
[0073] Application Example 1
[0074] The compound materials prepared in Example 1-1, Example 1-2 and Example 1-3 were used as adsorbents to adsorb uranyl ions. At pH = 4, the ion concentration was 1.0×10 −4 mol / L Zn 2+ Mg 2+ 、Ni + , Cu 2+ , VO 3− , Fe 3+ , Sr 2+ and UO2 2+ In the mixed aqueous solution, it was found that the three adsorbents all showed significant adsorption effects on uranyl ions, among which Examples 1-1, 1-2, and 1-3 had a significant adsorption effect on UO2 2+ The removal rates of VO 3− The removal rates are 15%, 17% and 25% respectively. It can be seen that the selectivity of the adsorbents in Examples 1-1 and 1-2 for uranium and vanadium is higher than that in Examples 1-3. In addition, the compound materials prepared in Examples 1-1, 1-2 and 1-3 have a higher selectivity for Zn 2+ Mg 2+ 、Ni + , Cu 2+ , Fe3+ , Sr 2+ The removal rate is less than 6%. It can be seen that the silica gel materials of Examples 1-1, 1-2 and 1-3 of the present invention can achieve a high selective adsorption and separation of uranium.
[0075] The reason why the removal rate of vanadium by the adsorbent of Example 1-3 is higher than that of Examples 1-1 and 1-2 is that the main pore size range of the silica gel material in Example 1-3 is larger, and the network distribution formed by the long-chain molecular combination of 4-vinylbenzaldehyde and biphenyl cyanide compounds connected in the silica gel segment is looser, and vanadium ions are easier to enter than in Examples 1-1 and 1-2; the selectivity of the silica gel material adsorbent prepared in Examples 1-1 and 1-2 for uranium and vanadium is improved to a certain extent compared with Example 1-3, which proves that the shortening of the chain length of the bridging agent and the connecting monomer in Examples 1-1 and 1-2 makes the grid tighter, and its main pore size distribution range is smaller, which has a better screening effect on the vanadium ions in the adsorption process.
[0076] This application example 1 shows that embodiments 1-1, 1-2, and 1-3 can be used for the efficient enrichment of uranyl ions in seawater.
[0077] Application Example 2
[0078] The four adsorbents of Examples 1-1, 1-2, 1-3, 2-1, and 2-2 were used to test the uranium-vanadium selectivity. At pH = 4, only UO2 2+ and VO 3− ions, the concentration of both is 1.0×10 −4 mol / L, the selectivity of four adsorbents was obtained. (u / v) They are 5.38, 5.53, 4.12, 4.0 and 3.84 respectively.
[0079] The reason for the gradual decrease in selectivity is that the chain length of the aldehyde bridging agent used in the synthesis examples 1-1, 1-2, 1-3, 2-1, and 2-2 gradually increases and the number of benzene rings of the aromatic ligand increases. The increase in chain length leads to an increase in the pore size of the silica gel, thereby reducing the screening effect for vanadium ions, resulting in a decrease in selectivity.
[0080] Application Example 3
[0081] The adsorbent prepared in Example 1-2 with higher uranyl selectivity was selected to test the uranium adsorption capacity in real seawater. Samples were taken on the 4th, 10th and 20th days, and the uranium adsorption capacities were tested and calculated to be 6.8, 14.1 and 23.6 mg / g, respectively, indicating that the adsorbent involved in the present invention has excellent uranium extraction performance in seawater.
[0082] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any modifications or equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A cross-grid structure functionalized silica gel material, characterized in that: The method is to react the compound shown in the structural formula I with an aromatic aldehyde or aliphatic aldehyde compound as a bridging agent and an aromatic cyano or aromatic carboxyl compound with a diamino group through a Schiff base reaction; the aromatic aldehyde or aliphatic aldehyde compound is an olefin compound or a halogen substituted compound; the cross-grid structure functionalized silica gel material has a cross-grid structure with adjustable pore size, and the grid pore size is distributed within 10-18Å; Wherein, structural formula I is: [(O 3 / 2 )Si(CH2)3NH[C2H4NH] p-1 C2H4NH2] a [(O 4 / 2 )Si] b [(O 3 / 2 )Si(CH2) m L] c [MSi(O 3 / 2 )] d ; Wherein L is -CN or S(CH2) y CN, y is an integer from 2 to 6; M is a substituent group selected from C 1-22 Alkyl, C 2-22 Alkenyl or C 1-22 alkylaryl; m is an integer from 2 to 12; p is an integer from 2 to 99; a, b, c, d are all integers, and the ratio of a+c:b is between 0.00001 and 100000; a and b are always present, and when c is greater than zero, the ratio of c to a+b is between 0.000001 and 10; silicon atoms, hydrogen atoms, straight or branched C atoms of other groups in formula I are present; 1-22 Alkyl, terminal group R 2 SiO 1 / 2 , cross-linking agent or chain R q Si(OR 1 ) g O k / 2 One or more of saturates the free valences of the silicate oxygen atoms, where R and R 1-2 Selected from linear or branched C 1-12 Alkyl, aryl or C 1-22 Alkyl aryl; k is an integer from 1 to 3, q is an integer from 1 to 2, g is an integer from 0 to 2, and satisfies g+k+q=4, and when end groups, crosslinking agents and / or polymer chains are present, their molar ratio to a+b+c+d is between 0 and 999:
1.
2. The cross-grid structure functionalized silica gel material according to claim 1, characterized in that: The aromatic aldehyde or aliphatic aldehyde compound is an olefin compound or a halogen substituted compound, and its structural formula is: or ; In the above structural formula, R a , R b , R c , R d , R', R'', R''' are selected from hydrogen, C 1-22 Alkyl, C 2-22 Alkenyl or C 1-22 One of the alkylaryl groups, X is a halogen; w is 0 or 1, and v is an integer from 0 to 7.
3. The cross-grid structure functionalized silica gel material according to claim 1, characterized in that: The structural formula of the aromatic cyano or aromatic carboxyl compound is one of the following structural formulas: ; In the above structural formula, T is one of alkenyl, aryl or its derivatives, n is an integer from 0 to 2; R1, R2, R3, R4, R1', R2', R3', R4' are respectively selected from one of hydrogen, -NH2, -CN, -COOH, and at least one is -CN or -COOH.
4. The cross-grid structure functionalized silica gel material according to claim 1, characterized in that: The structural formula A of the cross-grid structure functionalized silica gel material is one of the following structural formulas: ; ; In the above structural formula, R a , R b , R c , R d , R', R'', R''' are respectively selected from one of hydrogen, C1-22 alkyl, C2-22 alkenyl or C1-22 alkylaryl; w is 0 or 1, v is an integer from 0 to 7; T is one of alkenyl, aryl or their derivatives, and n is an integer from 0 to 2; R1, R2, R3, R4, R1', R2', R3', R4' are respectively selected from one of hydrogen, -NH2, -CN, -COOH, and at least one of them is -CN or -COOH; II is the structure remaining after the compound shown in structural formula I reacts with an aromatic aldehyde or a fatty aldehyde compound.
5. The cross-grid structure functionalized silica gel material according to claim 1, characterized in that: When an aromatic cyano compound is selected, the product after the Schiff base reaction is further subjected to a hydrolysis reaction.
6. A method for preparing a cross-grid structure functionalized silica gel material according to any one of claims 1 to 5, characterized in that: The steps include: (1) (R 3 O)3Si(CH2)3X' and the corresponding amine NH2[C2H4NH] p H reacts to form silane (R 3 O)3Si(CH2)3NH[C2H4NH] p H, X' are halogen elements, R 3 Selected from C 1-22 alkyl; (2) The silane coupling agent prepared in step (1) and the cyanosilane coupling agent (R 5 O)3Si(CH2) m L and / or MSi (OR 4 )3 is grafted onto the surface of silica gel to obtain a compound shown in structural formula I; wherein L is -CN or S(CH2) y CN, m is an integer from 2 to 12, y is an integer from 2 to 6; R 4 , R 5 Selected from C 1-22 alkyl; (3) subjecting the compound of structural formula I obtained in step (2) to a reflux reaction with an aromatic aldehyde or an aliphatic aldehyde compound under certain conditions to obtain a functionalized silica precursor; (4) The functionalized silica precursor prepared in step (3) is mixed with an aromatic cyano compound or an aromatic carboxyl compound having a diamino group in a solvent, and after reflux reaction at a certain temperature for a certain period of time, the precipitate is filtered, washed, and dried to obtain a cross-grid structured functionalized silica material.
7. The method for preparing a cross-grid structure functionalized silica gel material according to claim 6, characterized in that: When an aromatic cyano compound is selected, the product obtained in step (4) is further mixed with an acid in deionized water and then heated and stirred for a certain period of time. The precipitate obtained by the reaction is filtered, washed, centrifuged and dried to obtain a further carboxylated cross-grid structure functionalized silica gel material.
8. The method for preparing a cross-grid structure functionalized silica gel material according to claim 6, characterized in that: The reaction temperature of step (1) is 20-160°C, and the reaction time is 0.5-24h; the reaction temperature of step (2) is 20-160°C, and the reaction time is 0.5-24h; the reaction temperature of step (3) is 60-100°C, and the reaction time is 3-24h; the reaction temperature of step (4) is 50-80°C, and the reaction time is 2-12h.
9. The method for preparing a cross-grid structure functionalized silica gel material according to claim 6, characterized in that: (R 3 O)3Si(CH2)3X' and amine NH2[C2H4NH] p The molar ratio of H is 1:1.5~6; the mass ratio of the amount of the aromatic aldehyde or aliphatic aldehyde compound to the compound represented by the structural formula I is (0.01~10) mol:1g; the mass ratio of the amount of the aromatic cyano compound or aromatic carboxyl compound with a diamino group to the amount of the aromatic aldehyde or aliphatic aldehyde compound is 0.01~0.5:
1.
10. Use of the cross-grid structure functionalized silica gel material according to any one of claims 1 to 5, characterized in that: The cross-grid structure functionalized silica gel material is used as an adsorbent to adsorb uranium elements and to separate uranyl ions from vanadium ions.
Citation Information
Patent Citations
Titanium compound and process for producing optically active cyanohydrins
CN101039898A
Modified functional silica gel material as well as preparation method and application thereof
CN115624957A